Early diagnosis of asthma in young children by using non-invasive biomarkers of airway inflammation and early lung function measurements: study protocol of a case-control study - Jöbsis Quirijn; Klaassen Ester MM; van de Kant Kim DG; Nijhuis Annedien J; van Schayck Onno CP; Dompeling Edward (BMC, 2009)
Abstract Background Asthma is the most common chronic disease in childhood, characterized by chronic airway inflammation. There are problems with the diagnosis of asthma in young children since the majority of the children with recurrent asthma-like symptoms is symptom free at 6 years, and does not have asthma. With the conventional diagnostic tools it is not possible to differentiate between preschool children with transient symptoms and children with asthma. The analysis of biomarkers of airway inflammation in exhaled breath is a non-invasive and promising technique to diagnose asthma and monitor inflammation in young children. Moreover, relatively new lung function tests (airway resistance using the interrupter technique) have become available for young children. The primary objective of the ADEM study (Asthma DEtection and Monitoring study), is to develop a non-invasive instrument for an early asthma diagnosis in young children, using exhaled inflammatory markers and early lung function measurements. In addition, aetiological factors, including gene polymorphisms and gene expression profiles, in relation to the development of asthma are studied. Methods/design A prospective case-control study is started in 200 children with recurrent respiratory symptoms and 50 control subjects without respiratory symptoms. At 6 years, a definite diagnosis of asthma is made (primary outcome measure) on basis of lung function assessments and current respiratory symptoms ('golden standard'). From inclusion until the definite asthma diagnosis, repeated measurements of lung function tests and inflammatory markers in exhaled breath (condensate), blood and faeces are performed. The study is registered and ethically approved. Discussion This article describes the study protocol of the ADEM study. The new diagnostic techniques applied in this study could make an early diagnosis of asthma possible. An early and reliable asthma diagnosis at 2-3 years will have consequences for the management of the large group of young children with asthma-like symptoms. It will avoid both over-treatment of children with transient wheeze and under-treatment of children with asthma. This might have a beneficial influence on the prognosis of asthma in these young children. Besides, insight into the pathophysiology and aetiology of asthma will be obtained. Trial registration This study is registered by clinicaltrials.gov (NCT00422747).